Perirenal adipose tissue accumulation mediates the adverse impact of the atherogenic index of plasma on lower extremity peripheral arterial disease - Xiu Li Guo; Mei Tu; Xiu Ping Qiu; Wei Wang (Scientific Reports)
Abstract This study aims to evaluate the relationship between perirenal adipose tissue (PAT) accumulation and the risk of lower-extremity peripheral arterial disease (LEAD) and its potential mediating role in the association between the atherogenic index of plasma (AIP) and LEAD. 828 participants with type 2 diabetes mellitus (T2DM) were included in the final analysis. Perirenal fat thickness (PrFT) was assessed using unenhanced abdominal CT to estimate PAT mass. The diagnosis of LEAD was based on the ankle-brachial index (ABI), stenosis, or occlusion in the lower limb arteries. After full adjustment for potential confounders, PrFT negatively correlated with ABI (β = − 0.265, P < 0.001) and positively correlated with AIP (β = 0.121, P < 0.001). PrFT was identified as an independent risk factor for LEAD (OR 1.14, 95% CI 1.03–1.26, P = 0.010). Restricted cubic splines analysis further revealed a non-linear association between PrFT and risk of LEAD (P for overall = 0.015; P for nonlinear = 0.039). Additionally, PrFT mediated 15.9% and 12.5% of the adverse impacts of AIP on ABI and LEAD. Furthermore, sensitivity analyses excluding 141 newly diagnosed T2DM produced consistent results. PAT accumulation was independently associated with the risk of LEAD and partially mediated the adverse impacts of AIP on ABI and LEAD.